Qualidade de água utilizada para consumo em escolas e creches no município de São Carlos - SP - Scuracchio, Paola Andressa [UNESP]; Farache Filho, Adalberto [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
We know the importance of treating water for human consumption because changes in the physicochemical and / or biological has been associated with various health problems, the quality of water intended for human consumption must meet potability standards established by governmental decree 518/2004. The aim of this study was to evaluate the quality of water supplied schools and daycare in the city of São Carlos - SP. We selected 31 schools and kindergartens, and at intervals of 3 months, two water samples taken at three different points - network, tank and fi lter - totaling 186 samples, with an interval of three months, to verify possible differences in sampling points and at different times. The samples were evaluated for the following parameters: presence of total coliform and fecal coliform / E. coli count of heterotrophic bacteria, determination of pH, fl uoride, free residual chlorine, turbidity and color. The largest number of samples outside the standard for coliform was coming from the fi lters and the network, heterotrophic bacteria in most samples was taken out of standard fi lters. In the physical-chemical analysis of samples as many non-standard pH occurred in the network, network, and fl uoride in the fi lter pair in the fi lter to free chlorine and turbidity in the reservoir. The parameter with a larger sample size was inadequate fl uoride. We need more attention to the conservation, cleaning and maintenance of building reservoirs and fi lters in schools and kindergartens of San Carlos, since the water was considered unfi t for consumption.

Sabe-se da importância de se tratar a água destinada ao consumo humano, pois alterações nas características física, química e/ou microbiológica tem sido associadas a diversos problemas de saúde, além disso, a qualidade da água destinada ao consumo humano deve atender aos padrões de potabilidade estabelecidos pela Portaria n. 518/2004 do Ministério da Saúde. O objetivo desta pesquisa foi avaliar a qualidade da água utilizada em escolas e creches municipais da cidade de São Carlos – SP. Foram selecionados 31 estabelecimentos de ensino sendo 17 escolas e 14 creches; em cada uma delas foram colhidas duas amostras de água em três pontos distintos – 62 no ponto de entrada da rede, 62 do reservatório e 62 de fi ltros domésticos - totalizando 186 amostras, com intervalo de três meses, para verifi car possíveis diferenças nos pontos de colheita e em ocasiões diferentes. As amostras foram avaliadas para os seguintes parâmetros: presença de coliformes totais, Escherichia coli, contagem de bactérias heterotrófi cas mesó- fi las, determinação do pH, turbidez, cor, concentração de fl úor e de cloro residual livre. O maior número de amostras fora do padrão para coliformes totais foi proveniente dos fi ltros e da rede, para bactérias heterotrófi cas a maior parte das amostras fora do padrão foi colhida nos fi ltros. Nas análises físico-químicas o maior número de amostras fora do padrão ocorreu na rede para pH, na rede e no fi ltro para fl úor, no fi ltro para cloro residual livre e no reservatório para turbidez. O parâmetro com maior número de amostras inadequadas foi fl úor. É necessário maior atenção com a conservação, limpeza e manutenção dos reservatórios prediais e fi ltros nas escolas e creches de São Carlos, visto que, a água analisada estava imprópria para o consumo.
Quality of water used for consumption in schools and kindergartens in the municipality of São Carlos-SP
Quality of water used for consumption in schools and kindergartens in the municipality of São Carlos-SP
Keywords: Bacteriological quality; Coliforms; Heterotrophic bacteria; Physical and chemical parameters; Qualidade bacteriológica; Coliformes; Bactérias heterotrófi cas; Parâmetros físico-químicos